2022
DOI: 10.1590/1516-4446-2021-1926
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid system in social anxiety disorder: from pathophysiology to novel therapeutics

Abstract: Social anxiety disorder (SAD) is a highly prevalent psychiatric disorder that presents with an early age of onset, chronic disease course, and increased risk of psychiatric comorbidity. Current treatment options for SAD are associated with low response rates, suboptimal efficacy, and possible risk of adverse effects. Investigation of new neurobiological mechanisms may aid in the identification of more specific therapeutic targets for the treatment of this disorder. Emerging evidence suggests that the endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 202 publications
(255 reference statements)
0
1
0
Order By: Relevance
“…And it is attracting attention as a new intervention for treating anxiety disorders. There is potential for novel compounds in the endocannabinoid system to enhance the therapeutic armamentarium for SAD [25]. One study suggested that ayahuasca may modulate anandamide (AEA; an endocannabinoid) levels in people with SAD [26].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…And it is attracting attention as a new intervention for treating anxiety disorders. There is potential for novel compounds in the endocannabinoid system to enhance the therapeutic armamentarium for SAD [25]. One study suggested that ayahuasca may modulate anandamide (AEA; an endocannabinoid) levels in people with SAD [26].…”
Section: Pharmacotherapymentioning
confidence: 99%